The views and experiences of Grade 10 Life Sciences teachers on the compulsory practical examination - Furiwai, S.; Singh-Pillay, A. (University of the Free State, 2020)
With the introduction of the Curriculum Assessment and Policy Statement (CAPS) for Life Sciences (LS) in 2012 in South African schools, a practical examination has become compulsory in grades 10 and 11. The LS CAPS policy stipulates the types of practical work that needs to be conducted to develop specific process skills in learners. This case study explored grade 10 LS teachers’ views and experiences of the practical examination. This study was underpinned by two constructs from Rogan and Grayson’s theory of curriculum implementation, namely the profile of implementation pertaining to practical work and the capacity to innovate. Purposive sampling was used to generate data via questionnaires and individual interviews with grade 10 LS teachers at selected schools of the Umtshezi ward of Estcourt region. The findings highlight how physical resources, the mismatch between the medium of instruction and the learners’ home language, the culture of teaching and learning, teacher uncertainty and lack of confidence in performing practical work affect the kinds of practical work engaged in and their experiences of the practical examination. In addition, the dissonance between the intended LS CAPS policy document regarding types of practical work and the kinds of science process skills that ought to be developed in learners and the enacted LS CAPS policy document is exposed. Subsequently the disjuncture between policy intention and practice emphasises the need for continuous teacher professional development and a supportive school ethos.
Keywords: Capacity to innovate; Implementation; Life Sciences teachers; Practical examination; Practical work